Electrostatically Directed Long‐Range Self‐Assembly of Nucleotides with Cationic Nanoparticles To Form Multifunctional Bioplasmonic Networks. Issue 28 (17th May 2022) - Roy, Sumit; Adury, Venkata Sai Sreyas; Rao, Anish; Roy, Soumendu; Mukherjee, Arnab; Pillai, Pramod P.
Abstract: Precise control over interparticle interactions is essential to retain the functions of individual components in a self‐assembled superstructure. Here, we report the design of a multifunctional bioplasmonic network via an electrostatically directed self‐assembly process involving adenosine 5′‐triphosphate (ATP). The present study unveils the ability of ATP to undergo a long‐range self‐assembly in the presence of cations and gold nanoparticles (AuNP). Modelling and NMR studies gave a qualitative insight into the major interactions driving the bioplasmonic network formation. ATP‐Ca 2+ coordination helps in regulating the electrostatic interaction, which is crucial in transforming an uncontrolled precipitation into a kinetically controlled aggregation process. Remarkably, ATP and AuNP retained their inherent properties in the multifunctional bioplasmonic network. The generality of electrostatically directed self‐assembly process was extended to different nucleotide–nanoparticle systems. Abstract : A slow and steady aggregation process unveils the ability of ATP and other nucleotides to undergo a long‐range self‐assembly process in the presence of cationic gold nanoparticles and divalent ions. The inherent properties of ATP and AuNP are well retained in the self‐assembled bioplasmonic network.